The blood of Olympus [compact disc, unabridged] - Riordan, Rick (Riordan, Rick. Heroes of Olympus, 2014)
"The Greek and Roman demigods must simultaneously prevent the earth mother, Gaea, from waking and stop war from breaking out at Camp Half-Blood"--